Experience of Hypoxic Conditioning in Rehabilitation Programs for Patients with Chronic Occupational Lung Diseases: a Pilot Study - Xinliang Zhang; Evgeny Е. Achkasov; Elena N. Dudnik; Olga I. Rumyantseva; Oleg S. Glazachev (Вестник восстановительной медицины)
INTRODUCTION. Chronic occupational lung diseases (COLD) represent a serious medical and social problem associated with a high degree of comorbidity and systemic disorders, including cardiometabolic changes, pronounced oxidative stress, chronic inflammation, autonomous and immune dysregulation, and leading to disability and reduced quality of life. Hypoxic conditioning (HC), in particular, intermittent hypoxic-hyperoxic exposures (IHHE), which can improve adaptation mechanisms and reduce inflammatory processes, is a promising method of rehabilitation of patients with COLD, along with basic medication and physiotherapy.